Nitrate dynamics in a rural headwater catchment: measurements and modelling. Issue 4 (27th February 2013) - Smethurst, Philip J.; Petrone, Kevin C.; Langergraber, Günter; Baillie, Craig C.; Worledge, Dale; Nash, David
Abstract This study was designed to improve our understanding of, and mechanistically simulate, nitrate (NO3) dynamics in a steep 9.8 ha rural headwater catchment, including its production in soil and delivery to a stream via surface and subsurface processes. A two‐dimensional modelling approach was evaluated for (1) integrating these processes at a hillslope scale annually and within storms, (2) estimating denitrification, and (3) running virtual experiments to generate insights and hypotheses about using trees in streamside management zones (SMZs) to mitigate NO3 delivery to streams. Total flow was mathematically separated into quick‐ and slow‐flow components; the latter was routed through the HYDRUS software with a nitrogen module designed for constructed wetlands. Flow was monitored for two years. High surface‐soil NO3 concentrations started to be delivered to the stream via preferential subsurface flow within two days of the storm commencing. Groundwater NO3‐N concentrations decreased from 1.0 to less than 0.1 mg l−1 from up‐slope to down‐slope water tables, respectively, which was attributed to denitrification. Measurements were consistent with the flushing of NO3 mainly laterally from surface soil during and following each storm. The model accurately accounted for NO3 turnover, leading to the hypotheses that denitrification was a minor flux (<3 kg N ha−1) compared to uptake (98−127 kg N ha−1), and that SMZ trees would reduce denitrification if they lowered the water table. This research provides an example of the measurement and modelling of NO3 dynamics at a small‐catchment scale with high spatial and temporal resolution. Copyright © 2013 John Wiley & Sons, Ltd.